Figure Out the Online Discussion Activeness of Pre-Teacher Education Students - Fitri Indriani; Dwi Sulisworo (The Indonesian Institute of Science and Technology Research, 2022)
Online learning has been widely applied at various levels of education, including lectures for prospective teachers of elementary school students in Indonesia. However, student activity in learning is still an obstacle in this study. This study describes student activity in online discussions. The discussion was conducted three times with different topics. The activity can be examined from the students' posts during the three discussions. The three aspects of the activeness were the number of posts in each discussion, participation in the three discussion topics, and the number of words in each post. These results were analyzed descriptively to see the trend of active discussion. The findings of this study show the role of lecturers in providing appreciation and feedback. The role of friends in reinforcing other friends' opinions determines the increase in activity in discussions. Social presence, self-esteem engagement, and social learning are essential issues in increasing this activity.